[Optimising the COVID-19 vaccination programme for maximum short-term impact]. Report to JCVI on estimated efficacy of a single dose of Pfizer BioNTech (BNT162b2 mRNA) vaccine and of a single dose of ChAdOx1 vaccine (AZD1222) Annex A, (2021) - Unknown
No abstract available